Towards the Use of Modern and Basic Skills in Teaching Arabic to Non-Native Speakers at The Junior Secondary Schools’ Level in Nigeria/ نحو استخدام المهارات الأساسية الحديثة في تعليم اللغة العربية للناطقين بغيرها في المرحلة المتوسطة في نيجيريا - Ahmad Garba (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2022)
Language is one of the features that human being is differed from other creatures, and it constitutes a great cognitive manifestation and mental characteristics. On this basis, the process of teaching languages in general requires necessary skills and techniques, so also the teaching of Arabic to non-native speakers requires basic skills and strategies. The main objective of this paper is to highlight the needs and justifications of using modern approaches towards teaching Arabic language to non-native speakers in junior secondary schools in Nigeria. The teaching process does not dispense with the necessary basic skills, which are the basis on which teachers build their activities in the classroom to send information and ideas to the minds of learners, and these skills did not stop inside the classroom only, but even outside it. These basic skills include: the skill of set induction, skill of classroom management, skill of asking questions, skill of reinforcement, skill of using chalkboard, and the skill of using various teaching method. إن اللغة من المميزات التي انفرد الإنسان بها عن غيره من سائر المخلوقات, وهي تشكل أعظم ما تتجلى فيه مميزاته العقلية.وهي من الحاجات الأساسية اللإنسان, بها يقوم بينه وبين غيره علاقة تبادلية وثيقة. وعلى هذا الأساس تحتاج عملية التعليم اللغات بوجه عام إلى مهارات وتقنيات الازمة كما تتطلب تعليم اللغة العربية للناطقين بغيرها مهارات واستراتيجيات أساسية بوجه خاص. هدفت هذه الورقة إلفاء الضوء على مبررات استخدام المهارات الأساسية في تعليم اللغة العربية للناطقين بغيرها نحو الطلبة المرحلة المتوسطة في نيجيريا.لا تستغني عملية التدريس عن المهارات الأساسية الازمة، وهي الأساس التي يبني عليها المدرسين عملياتهم  داخل الفصل لإرسال المعلومات والأفكار إلى أذهان المتعلمين، وهذه المهارات لم تقف داخل الغرفة الصف فحسب،بل حتى خارجها.  وتحتوي هذه الورقة الي مقدمة ومنهجية البحث ومفهوم التدريس وأهمية المهارات التدريس ثم البيان حول بعض المهارات التدريس الأساسية في عملية التدريس ثم نتائج البحث والمقترحات والخاتمة والمراجع.